Peningkatan Kapasitas Manajemen dan Entreprenuer Islami bagi Pemuda di Desa Persiapan Penanggak Batulayar - Mashur Mashur; Muhammad Yakub; Dedi Riswandi (Universitas Mataram, 2022)
The purpose of this community service program is to provide knowledge about the importance of management, organization, the importance of entrepreneurship for the community, especially youth. The methods used in this activity as part of the mentoring are light discussions, lectures, discussions about the importance of management knowledge, local potential to develop an entrepreneurial spirit as well as entrepreneurial and economic insights in Islamic teachings. The result of this community service activity is that the community in Preparation village, Penanggak village, can develop knowledge about the material presented by seeing the enthusiasm and appreciation of the participants, the youth who participated from the many questions during the discussion. Awareness of the importance of skills in managing the 'village' organizational unit, and inculcating the entrepreneurial spirit of the community and youth are important factors to build and develop the village and the community in it so that it will soon become a definitive village and an independent village. Assistance from various parties is needed in order to increase management capacity and entrepreneurial spirit in the Preparation village of Penanggak village, Batulayar sub-district.